Heart valve tissue engineering: how far is the bedside from the bench? - Sanz-Garcia, Andres; Oliver-de-la-Cruz, Jorge; Mirabet, Vicente; Gandía, Carolina; Villagrasa, Alejandro; Sodupe, Enrique; Escobedo-Lucea, Carmen (Expert reviews in molecular medicine, 2015)
Heart disease, including valve pathologies, is the leading cause of death worldwide. Despite the progress made thanks to improving transplantation techniques, a perfect valve substitute has not yet been developed: once a diseased valve is replaced with current technologies, the newly implanted valve still needs to be changed some time in the future. This situation is particularly dramatic in the case of children and young adults, because of the necessity of valve growth during the patient's life. Our review focuses on the current status of heart valve (HV) therapy and the challenges that must be solved in the development of new approaches based on tissue engineering. Scientists and physicians have proposed tissue-engineered heart valves (TEHVs) as the most promising solution for HV replacement, especially given that they can help to avoid thrombosis, structural deterioration and xenoinfections. Lastly, TEHVs might also serve as a model for studying human valve development and pathologies.
Keywords: kolagen; Fibrin; tkáňové podpůrné struktury; Tissue Engineering; fibrin; ovce; Collagen; indukované pluripotentní kmenové buňky; Fetal Blood; Heart Valve Prosthesis; dítě; bioprotézy; Child; Tissue Scaffolds; Swine; kyselina hyaluronová; zvířata; Bioprosthesis; Humans; Hyaluronic Acid; srdeční chlopně umělé; endoteliální buňky; tkáňové inženýrství; Induced Pluripotent Stem Cells; prasata; Sheep; srdeční chlopně; fetální krev; Heart Valves; lidé; Endothelial Cells; Animals